Ask Question
4 November, 17:19

1 (6x - 9) = (4x - 6)

0
Answers (2)
  1. 4 November, 18:20
    0
    exact: x=3/2, decimal: x=1.5, mixed number x=1 1/2
  2. 4 November, 19:13
    0
    1 (6x-9) = (4x-6)

    One solution was found:

    x = 3/2 = 1.500

    Rearrange:

    Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:

    1 * (6*x-9) - ((4*x-6)) = 0

    Step by step solution:

    Step 1:

    Step 2:

    Pulling out like terms:

    2.1 Pull out like factors:

    6x - 9 = 3 • (2x - 3)

    Equation at the end of step 2:

    3 • (2x - 3) - (4x - 6) = 0

    Step 3:

    Equation at the end of step 3:

    2x - 3 = 0

    Step 4:

    Solving a Single Variable Equation:

    4.1 Solve : 2x-3 = 0

    Add 3 to both sides of the equation:

    2x = 3

    Divide both sides of the equation by 2:

    x = 3/2 = 1.500

    One solution was found:

    x = 3/2 = 1.500
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “1 (6x - 9) = (4x - 6) ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers